Nursing Interventions in Emergency Medicine: Bridging the Gap Between Rapid Response and Quality Care - aljauid, Safrah Awad Awaif; Al-Hidban, Fahd Abdullah Saleh; Al bishi, Saeedah Saeed Zamim; Alkaabi, Sabah Salem Aboud; Al-Aklobi , Shatha Abdullah; Al-Aklabi, Amira Mishaal Saad; Al Jumeaan , Saada Mahdi; Al-Nas, Roqya Ali; Aljuaid, Nada Awad Owayf; Al-Shahrani, Majed Ali Mohammed (Journal of Ecohumanism, 2024)
Emergency nursing plays a pivotal role in ensuring timely and effective care in critical situations. This article examines the impact of nursing interventions in emergency medicine, highlighting their importance in balancing rapid response with the delivery of high-quality care. It delves into strategies such as advanced triage systems, pain management techniques, resuscitation protocols, and the integration of technology to enhance care efficiency. Emphasis is placed on training, teamwork, and overcoming challenges like staffing shortages and emergency department overcrowding. By bridging the gap between speed and quality, nursing interventions contribute significantly to improved patient outcomes and the overall effectiveness of emergency medicine.